Therapeutic efficacy of intravenous immunoglobulin in ulcerative colitis - LONG Qian; WANG Zongkui; LI Changqing; ZHANG Rong (Zhongguo shuxue zazhi)
[Objective] To explore the therapeutic effects of intravenous immunoglobulin (IVIG) on dextran sodium sulfate (DSS)-induced ulcerative colitis (UC). [Methods] C57BL/6 mice were randomly assigned to the control group, the DSS group (model) and the DSS+IVIG group (treatment). The DSS group and the DSS+IVIG group received 3% DSS in drinking water to establish the acute UC mouse model. During the experiment, the DSS+IVIG group received IVIG (1 g/kg/2d) via tail vein injection, while the DSS group received equivalent saline via tail vein injection at the same dose and frequency. The symptoms of the mice were observed, body weight changes were recorded, and the disease activity index (DAI) was calculated daily. At the end of the experiment, hematoxylin-eosin (HE) staining was used to observe the pathological changes and inflammatory cell infiltration of colon tissue; Periodic acid-Schiff (PAS) staining was used to quantify the number of goblet cells; Luminex was used to detect the levels of inflammatory-related cytokines (such as TNF-α, IL-6 and MMPs) in colon; western blot and qRT-PCR were respectively used to detect the protein expression and mRNA levels of tight junction proteins (ZO-1, Occludin, Claudin-3). [Results] DSS induced weight loss, diarrhea, bloody stool, increased DAI score, and shortened colon length in mice. Compared with DSS group, after the administration of IVIG, the DAI score was significantly reduced (P<0.001), colon length was increased (P<0.001), infiltration of inflammatory cells and pathological damage were alleviated in colonic mucosa (P<0.001), the number of goblet cells were increased (P<0.05), and the levels of inflammatory-related cytokines TNF-α, IL-6, IL-6R, MMP2, MMP3 and Chitinase3like1 were decreased (all P<0.05). Western blot and qRT - PCR results showed that IVIG significantly up-regulated the protein expression of ZO-1, Occludin and claudin-3 (all P<0.05) and the mRNA levels of ZO-1 and Occludin (all P<0.05). [Conclusion] IVIG has protective effects on colitis by inhibiting the pathological release of inflammatory-related cytokines such as TNF-α, IL-6 and MMPs and restoring the integrity of intestinal barrier.